FACTORS AFFECTING FRAUD PREVENTION AND ITS IMPLICATION TO THE QUALITY OF FINANCIAL STATEMENTS - Monika Budiman; Choirul Anwar; Sudjono Sudjono (Journal of Applied Finance & Accounting, 2021)
The study aims to determine the effect of internal control, internal audit, risk-based audit, audit committee, and whistleblowing system on fraud prevention and its implications to the quality of financial statements. The sample consisted of 7 companies from 12 populations of chemical sub-sector companies and 5 companies from 10 populations of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange in 2018. Data were collected using questionnaires with 154 respondents. The analysis technique using Structural Equation Modeling (SEM) and processed with Lisrel 8.8. The results indicate that, partially, internal control, internal audit, risk-based audit, and audit committee have a positive and significant effect on fraud prevention, while the whistleblowing system partially has a negative and insignificant effect. However, simultaneously, the direct effect of internal control, internal audit, risk-based audit, audit committee, and whistleblowing system on fraud prevention have a positive and significant effect. The results also show partially internal control, internal audit, whistleblowing system, and fraud prevention have a positive and significant effect on the quality of financial statements while risk-based audit has a positive but not significant effect and the audit committee has a negative and insignificant effect on the quality of financial statements. However, simultaneously, the indirect effect of internal control, internal audit, risk-based audit, audit committee, whistleblowing system on the quality of financial statements through fraud prevention have a positive and significant effect.